Hypoxia enhances human myoblast differentiation: involvement of HIF1α and impact of DUX4, the FSHD causal gene - Thuy-Hang Nguyen; Lise Paprzycki; Alexandre Legrand; Anne-Emilie Declèves; Philipp Heher; Maelle Limpens; Alexandra Belayew; Christopher R. S. Banerji; Peter S. Zammit; Alexandra Tassin (Skeletal Muscle, 2023)
Abstract Background Hypoxia is known to modify skeletal muscle biological functions and muscle regeneration. However, the mechanisms underlying the effects of hypoxia on human myoblast differentiation remain unclear. The hypoxic response pathway is of particular interest in patients with hereditary muscular dystrophies since many present respiratory impairment and muscle regeneration defects. For example, an altered hypoxia response characterizes the muscles of patients with facioscapulohumeral dystrophy (FSHD). Methods We examined the impact of hypoxia on the differentiation of human immortalized myoblasts (LHCN-M2) cultured in normoxia (PO2: 21%) or hypoxia (PO2: 1%). Cells were grown in proliferation (myoblasts) or differentiation medium for 2 (myocytes) or 4 days (myotubes). We evaluated proliferation rate by EdU incorporation, used myogenin-positive nuclei as a differentiation marker for myocytes, and determined the fusion index and myosin heavy chain-positive area in myotubes. The contribution of HIF1α was studied by gain (CoCl2) and loss (siRNAs) of function experiments. We further examined hypoxia in LHCN-M2-iDUX4 myoblasts with inducible expression of DUX4, the transcription factor underlying FSHD pathology. Results We found that the hypoxic response did not impact myoblast proliferation but activated precocious myogenic differentiation and that HIF1α was critical for this process. Hypoxia also enhanced the late differentiation of human myocytes, but in an HIF1α-independent manner. Interestingly, the impact of hypoxia on muscle cell proliferation was influenced by dexamethasone. In the FSHD pathological context, DUX4 suppressed HIF1α-mediated precocious muscle differentiation. Conclusion Hypoxia stimulates myogenic differentiation in healthy myoblasts, with HIF1α-dependent early steps. In FSHD, DUX4-HIF1α interplay indicates a novel mechanism by which DUX4 could interfere with HIF1α function in the myogenic program and therefore with FSHD muscle performance and regeneration.